Microwave-assisted conversion of agro-industrial copra residue oil to diesel engine compatible fatty acid methyl esters - Ilham, Zul; Hakimi, M.I.; Mansor, M.R.A.; Goembira, F. (IOP Publishing, 2019)
Due to the increasing concern towards fossil fuel reserve and its fluctuating price, many countries shifted towards producing biodiesel as an alternative green fuel. In this study, the main objective is to synthesis biodiesel from coconut copra, an agro-industrial residue, as potential feedstock using different transesterification techniques, namely stirring mechanical-assisted technique (SAT), ultrasonic-assisted technique (UAT), and microwave-assisted technique (MAT). The current study will show comparison between the biodiesel yields, fatty acid methyl ester (FAME) compositions and fuel properties of the transesterification techniques used. The result showed that the copra residue biodiesel (CRB) using SAT produced the highest yield of biodiesel compared to UAT and MAT, which are 96.85% (±0.69), 93.79% (±1.00), and 91.76% (±0.87), respectively. Furthermore, different volumes of solvent and catalyst amount were found to affect the biodiesel yields, relatively. On the other hand, for FAME compositions, insignificant results were observed. The fuel properties in CRB complied with the international standards, thus, showing high compatibility to be used in diesel engine.